Sand bar opening in a coastal lagoon (Iquipari) in the northern region of Rio de Janeiro State: hydrological and hydrochemical changes - SUZUKI,M. S. (2002)
The aim of this paper was to verify hydrological and hydrochemical changes in the Iquiparí Lagoon water column, during three months, as related to an artificial sand bar opening. A drastic reduction in water volume occurred 28 hours after the sand bar opening, exposing the bottom sediment. This was densely colonized by submerged aquatic plants, which were dominant in the ecosystem metabolism, specially near the sand bar. An increase in salinity values, and dissolved and total nutrient concentrations, was observed during the sand bar opening period. In contrast, chlorophyll a concentration decreased. These changes were associated with: 1) mix of remained brackish and marine waters; 2) nutrient release from sediments by physical processes; and 3) submerged plant death. After the sand bar closure, lagoon metabolism was completely regulated by a dense phytoplankton community. We observed that the sand bar opening resulted in an extensile replacement of the lagoon's water and a change in the community mainly responsible for the ecosystem metabolism.